Pelatihan Pengembangan Usaha Koperasi Rumah Sakit Citra Mandiri Dr. Cipto di Jakarta - Sugiyanto Ikhsan; Udin Hidayat; Mohammad Fahreza (E-Coops-Day, 2023)
In the era of globalization and increasingly fierce competition, business entity companies in various sectors must continue to adapt in developing their business. That is, it is important for a cooperative to carry out business development, which is done to ensure the sustainability and success of the cooperative. In a competitive business world, cooperatives need to continue to develop their businesses in order to remain relevant and competitive. So there is a need for training to further strengthen business performance in conducting business development in cooperatives. For the business development training method at the RSCM Cooperative, Dr. Cipto Jakarta uses an interactive and practical approach, where participants are involved in group discussions, case studies, simulations, and practical exercises. With this training, participants can understand the implementation of business development through market penetration, product development, market development, and product diversification in addition to positive impacts and business alternatives that can be done. In addition, participants are encouraged to try to implement things that need to be considered when conducting business development.